Modification of the isotopic and geochemical compositions of accessory minerals controlled by microstructural setting - Clark, Chris; Taylor, Richard J.M.; Roberts, M.P.; Harley, S.L. (2024)
In situ age and trace element determinations of monazite, rutile and zircon grains from an ultrahigh temperature (UHT) metapelite-hosted leucosome from the Napier Complex using laser split-stream analysis reveal highly variable behaviour in both the U–Pb and trace element systematics that can be directly linked to the microstructural setting of individual grains. Monazite grains armoured by garnet and quartz retain two concordant ages 2.48 and 2.43 Ga that are consistent with the previously determined ages for peak UHT metamorphism in the Napier Complex. Yttrium in the armoured grains is unzoned with contents of ~700 ppm for the garnet-hosted monazite and in the range 400–1,600 ppm for the monazite enclosed within quartz. A monazite grain hosted within mesoperthite records a spread of ages from 2.43 to 2.20 Ga and Y contents ranging between 400 and 1,700 ppm. This grain exhibits core to rim zoning in both Y and age, with the cores enriched in Y relative to the rim and younger ages in the core relative to the rim. A monazite grain that sits on a grain boundary between mesoperthite and garnet records the largest spread in ages—from 2.42 to 2.05 Ga. The youngest ages in this grain are within a linear feature that reaches the core and is connected to the grain boundary between the garnet and mesoperthite; the oldest ages are observed where monazite is in contact with garnet. Yttrium in the grain is enriched in the core and depleted at the rim with the strongest depletions where monazite is adjacent to grain boundaries between the silicate minerals or in contact with garnet. The unarmoured monazite grains have lower intercept ages of 1.85 Ga, which overlaps with the bulk of ages determined from the rutile and is coincident with a previously reported zircon age obtained through depth profiling from the Napier Complex. The age and chemical relationships outlined above illustrate decoupling between the geochemical and geochronological systems in monazite. Individual grains are suggestive of a range of processes that modify these systems, including volume diffusion, flux-limited diffusion and fluid-enhanced recrystallization, all operating at the scale of a single thin section and primarily controlled by host mineral microstructural setting. These findings illustrate how the development of simple partitioning coefficients (cf. garnet/zircon) and geospeedometry based on experimentally determined diffusion coefficients on grain separates may not be achievable. However, it highlights the utility of combining age and trace element concentrations from multiple accessory minerals with microstructural information when trying to build a complete history of tectonothermal events experienced by an ancient rock system that has undergone a prolonged history of thermal, deformational and fluid flow events.